+0

# 3x+2(x+7)-5=4(x+3)-3(x+1)

0
266
4

3x+2(x+7)-5=4(x+3)-3(x+1)

Guest Jan 20, 2015

#1
+808
+10

Order of operations:

1. Solve what's inside the paranthesis

2. Multiply (*) / divide (:)

3. Add (+) / subtract (-)

3x + 2(x + 7) - 5 = 4(x + 3) - 3(x + 1)

3x + 2x +14 - 5 = 4x + 12 - 3x - 3

5x + 9 = x + 9      You'd typically like to have the x'es on the lift side

Move the x to the left, and the nine on the left side over to the right side

4x = 0

x = 0

Tetration  Jan 20, 2015
Sort:

#1
+808
+10

Order of operations:

1. Solve what's inside the paranthesis

2. Multiply (*) / divide (:)

3. Add (+) / subtract (-)

3x + 2(x + 7) - 5 = 4(x + 3) - 3(x + 1)

3x + 2x +14 - 5 = 4x + 12 - 3x - 3

5x + 9 = x + 9      You'd typically like to have the x'es on the lift side

Move the x to the left, and the nine on the left side over to the right side

4x = 0

x = 0

Tetration  Jan 20, 2015
#2
+85958
0

CPhill  Jan 20, 2015
#3
+808
0

Thx, I try to find a good balance between efficient writing and holistic and pedagogic answers :)

Indeed, I believe I learn some English and some math along the way.

I'm from Norway, you know :)

Tetration  Jan 20, 2015
#4
+85958
0

"Holistic'..."Pedagogic"......

Hey..I'm from Louisiana....don't you realize that, down here, we have to use a dictionary for words that contain 3 or more syllables???       (LOL!!!)

CPhill  Jan 20, 2015

### 29 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details